Molecular docking, quantum chemical computational and vibrational studies on bicyclic heterocycle "6-nitro-2, 3-dihydro-1, 4-benzodioxine": Anti-cancer agent. (June 2020) - Shafi, Aayisha; Timiri Sathyamurthy, Renuga Devi; Seetharaman, Janani; Sambanthan, Muthu; Murugesan, Raja; Sundaram, Sevvanthi; Bhanumathy Ramarathinam, Raajaraman
Graphical abstract: Highlights: Molecular docking has been performed for the biological activity of 6N3DB. Vibrational studies were performed to know chemically active atoms of 6N3DB. HOMO-LUMO has been explained for NLO, corrosion inhibition and electronic properties. ELF, LOL, RDG have been visualized and steric, vdW, intramolecular interactions are explained. Abstract: The heterocyclic aromatic compounds are primarily used to make pharmaceutical and agrochemicals. In addition, these compounds can be chosen as antioxidants, corrosion inhibitors, electro and opto-electronic devices, polymer material, dye stuff, developers, etc. On the account of this, the heterocyclic aromatic 6-nitro-2, 3-dihydro-1, 4-benzodioxine (6N3DB) was chosen and the structure is optimized to predict the important properties of it. The structural parameters such as bond length and bond angle have been obtained by DFT/B3LYP/6-311++G(d, p) basis set to know the geometry and orientation of 6N3DB. The molecule has been characterized by FT-IR and FT-Raman spectroscopic techniques to predict the functional groups, vibrational modes and aromatic nature of 6N3DB. The chemical shifts of 1 H and 13 C have been obtained experimentally and compared with the theoretical data. The parameters such as the band gap between HOMO-LUMO orbitals, λmax, and electron transition probability in frontier orbitals have been estimated to know the NLO and corrosion inhibition activity. HOMO-LUMO orbital diagram has been obtained for different energy levels and their band gap energies have been compared with UV–vis band gap values. The chemical significance of the molecule has been explained using ELF, LOL, and RDG. The binding energy and intermolecular energy values indicate that the title compound possesses anti-cancer property through hydrolase inhibition activity.